Single-Step Methylation of Chitosan Using Dimethyl Carbonate as a Green Methylating Agent - Hemming, Ellen B.; Masters, Anthony F.; Perosa, Alvise; Selva, Maurizio; Maschmeyer, Thomas (Molecules (Basel, Switzerland), 2019)
N,N,N-Trimethyl chitosan (TMC) is one chitosan derivative that, because of its improved solubility, has been studied for industrial and pharmaceutic applications. Conventional methods for the synthesis of TMC involve the use of highly toxic and harmful reagents, such as methyl iodide and dimethyl sulfate (DMS). Although the methylation of dimethylated chitosan to TMC by dimethyl carbonate (DMC, a green and benign methylating agent) was reported recently, it involved a formaldehyde-based procedure. In this paper we report the single-step synthesis of TMC from chitosan using DMC in an ionic liquid. The TMC synthesised was characterised by 1H NMR spectroscopy and a functionally meaningful degree of quaternisation of 9% was demonstrated after a 12-h reaction time.